2020
DOI: 10.1158/1538-7445.am2020-3442
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3442: Multimodal mapping of the immune landscape in human pancreatic cancer

Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) is the fourth leading cause of cancer related death in the US. Unfortunately, recent clinical trials using immunotherapy targeting the highly immunosuppressive tumor microenvironment have showed disappointing results, as there is no method to predict which patients will respond to therapy. More recently, the development of single cell technology has allowed for in-depth profiling at the cellular level using small amounts of tissue, raising the potential to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Therefore, we hypothesized that LOR increases inflammatory signaling by promoting GPR68 activation in CAFs. To further support that GPR68 is preferentially expressed in CAFs, we analyzed human PDAC single cell sequencing data from Steele et al (20). As observed in the Peng et al (2019) dataset, GPR68 was most highly enriched in human PDAC CAFs (Fig.…”
Section: Gpr68 Is Preferentially Expressed On Human Pdac Cafsmentioning
confidence: 73%
See 4 more Smart Citations
“…Therefore, we hypothesized that LOR increases inflammatory signaling by promoting GPR68 activation in CAFs. To further support that GPR68 is preferentially expressed in CAFs, we analyzed human PDAC single cell sequencing data from Steele et al (20). As observed in the Peng et al (2019) dataset, GPR68 was most highly enriched in human PDAC CAFs (Fig.…”
Section: Gpr68 Is Preferentially Expressed On Human Pdac Cafsmentioning
confidence: 73%
“…S4D). In addition to being expressed on CAFs, reanalysis of the CAF cluster in the human PDAC single cell sequencing by Steele et al (20) indicated that Gpr68 is not highly expressed on pericytes (RGS5 marker), supporting that it is a fibroblast-specific marker (Supplemental Fig. S4E-S4G).…”
Section: Gpr68 Is Preferentially Expressed On Human Pdac Cafsmentioning
confidence: 98%
See 3 more Smart Citations